Analisa Numerik Kapasitas Geser Dinding Geser Pelat Baja Dengan Bukaan Untuk Rasio Tinggi–Lebar Panel (B/H ≥ 1) - Nidiasari, Nidiasari (Jurnal Bangunan, Konstruksi & Desain, 2025)
Steel Plate Shear Wall (SPSW) is a lateral force resisting system developed as an alternative to reinforced concrete shear walls, especially in multi-storey building structures. The presence of openings in the plate panel, such as for building access and utility needs, has the potential to reduce the structural capacity and change the force transfer mechanism. Therefore, this study aims to evaluate the effect of openings on the shear capacity and stress distribution of steel plate shear walls with a panel geometry ratio of B/H ³ 1. The study was conducted through finite element-based numerical modeling. Variations in the B/H ratio were analyzed by maintaining the same percentage of openings, while lateral loading was given by displacement control until it reached a drift of 4% of the panel height. Load-displacement data and stress contours were obtained as the main results to evaluate the structural response to lateral loads. The simulation results show that although the presence of openings triggers stress concentration in the opening corner area and affects the distribution of diagonal tension mechanisms, the shear capacity in panels with a B/H ratio ≥ 1 still increases. This condition is caused by the wider panel geometry, so that the remaining effective plate area is still able to withstand lateral forces and maintain stable shear force transfer. In addition, shear walls with B/H > 1 exhibit a wider diagonal strain pattern distributed in both directions, thus reducing the stiffness reduction due to openings.